PMRI APPROACH (REALISTIC MATHEMATICS EDUCATION APPROACH OF INDONESIA) TO IMPROVE UNDERSTANDING MATHEMATICAL ABILITY AND DISPOSITION SMP STUDENT - Kesumawati, Nila (Jurnal Dosen Universitas PGRI Palembang)
AbstractThis aim of this study to determine the influence of PMRI approach to improvement of understanding and mathematical disposition. Experimental design used is a Control Group Pretest-posttest design. Samples were randomly selected from three grade schools that ranked high school ranking, medium school rankings, and low scholls rankings. From each of the schools taken two classes; one class as an experimental class (PMRI approach) and one more class as a conrol class (conventional learning). Analysis of test data using two-ways ANOVA. Based on the data analysis, it can be concluded that the improvement of mathematical understanding ability and disposition of student who got PMRI approach is higher than students who had conventional mathematic (CMT) approach, by overall students, school rank, and students basic mathematical knowledge. Keywords: realistic mathematics education Indonesia (PMRI), mathematical understanding (MU), mathematical disposition (MD), school rank (SR), and students basic mathematic knowledge (BMK).